Evaluation of mitochondrial respiratory function in rat cardiomyocytes under different glucose conditions, using an extracellular flux analysis method. (13th November 2018) - Tsubone, Hirokazu; Mutoh, Tatsushi
Summary: We studied the effect of glucose supply on mitochondrial respiratory function (MRF) of neonatal rat cardiomyocytes, using a novel extracellular flux analysis. Fundamental respiratory parameters regarding oxygen consumption rate in mitochondria showed glucose concentration‐dependent changes, where a significant increase or decrease in these parameters was observed to be associated with glucose concentrations ranging between 10% and 1000% of the concentration used in standard medium (3151 mg/L), respectively. By contrast, the extracellular acidification rate, a parameter of anaerobic activity, was shown to decrease under low‐glucose conditions, whereas it increased after inhibiting complex V (ATP synthase) under the same glucose conditions. These findings provide a beneficial basis for various experimental studies on mitochondrial metabolism in cardiomyocytes.